Cattle, Land, People, and Accountability Systems: The Makings of a Values-based Organisation. (2nd January 2017) - Dillard, Jesse; Pullman, Madeleine
ABSTRACT: An in-depth case study of a natural beef cooperative describes a management information and accountability system (MIAS) that emerged from, and facilitates the nurturing of, a values-based organisation's core values. Sustaining the family ranching culture and community represents the core value upon which the values-based agricultural coop is founded. Responsible people, land and animal management are central elements in sustainable ranching operations. The MIAS is designed to support the social and environmental objectives as well as to maintain the economic viability of the ranchers that make up this social enterprise. The MIAS is the key to linking organisational core values, both intrinsic and extrinsic, through its products, to its customers. Unique product attributes are acquired through the application of appropriate production process, maintained throughout the supply chain, and their presence certified to the end customer. The MIAS is designed to motivate and reward achieving these values-based characteristics and processes. The case study provides a unique example of a MIAS that is grounded in, and constructed to specifically address, the core values-based objective and, in doing so, to facilitate economic sustainability.